Verbs, Bones, and Brains Interdisciplinary Perspectives on Human Nature - Fuentes, Agustín (University of Notre Dame Press, 2017)
Verbs, Bones, and Brains engages in an interdisciplinary conversation about God, creation, evolution, and human nature